Vaginal cuff dehiscence: a randomized trial comparing robotic vaginal cuff closure methods. Issue 4 (December 2016) - Landeen, Laurie; Hultgren, Elizabeth; Kapsch, Taylor; Mallory, Paul
Abstract The purpose of this study is to compare the rate of vaginal cuff dehiscence between two different methods of closure in patients undergoing robotic-assisted total laparoscopic hysterectomy and explore variables related to postoperative breakdown. This was a prospective, randomized controlled study with two arms. The control group (Arm 1) underwent single-layer continuous closure while the study group (Arm 2) had three additional imbricating figure-of-X sutures placed in addition to the standard protocol. Of the 263 patients who completed the study, 4 patients (1.49 %) experienced dehiscence of the vaginal cuff. Three of the four patients with dehiscence received the standard single vaginal cuff closure (Arm 1) and the one remaining case of dehiscence underwent the protocol with additional sutures (Arm 2). All patients who experienced dehiscence were current smokers. Our study suggests that there may be benefit in adding additional sutures to the standard single-layer vaginal cuff closure procedure. Physicians should evaluate smoking status before deciding on a vaginal cuff closure method.